2012
DOI: 10.1111/gcb.12075
|View full text |Cite
|
Sign up to set email alerts
|

Above‐ and belowground linkages in Sphagnum peatland: climate warming affects plant‐microbial interactions

Abstract: Peatlands contain approximately one third of all soil organic carbon (SOC). Warming can alter above- and belowground linkages that regulate soil organic carbon dynamics and C-balance in peatlands. Here we examine the multiyear impact of in situ experimental warming on the microbial food web, vegetation, and their feedbacks with soil chemistry. We provide evidence of both positive and negative impacts of warming on specific microbial functional groups, leading to destabilization of the microbial food web. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
212
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(221 citation statements)
references
References 69 publications
7
212
2
Order By: Relevance
“…At the Bog site, the increase in air temperature was also associated with an increase in peat water content (Table 3). This result is surprising since most studies on experimental warming reported a decrease or no effect on peat moisture (Hollister et al, 2006;Dorrepaal et al, 2009;Bokhorst et al, 2011;Delarue et al, 2011a;Jassey et al, 2013). The question is therefore whether this effect was due to an experimental artefact or whether it results from a thermodynamic constraint.…”
Section: Experimental Air Warming Enhances the Discrepancy Of Peat Tementioning
confidence: 90%
See 1 more Smart Citation
“…At the Bog site, the increase in air temperature was also associated with an increase in peat water content (Table 3). This result is surprising since most studies on experimental warming reported a decrease or no effect on peat moisture (Hollister et al, 2006;Dorrepaal et al, 2009;Bokhorst et al, 2011;Delarue et al, 2011a;Jassey et al, 2013). The question is therefore whether this effect was due to an experimental artefact or whether it results from a thermodynamic constraint.…”
Section: Experimental Air Warming Enhances the Discrepancy Of Peat Tementioning
confidence: 90%
“…Such a pattern is known as the enzymatic latch theory (Freeman et al, 2001). Following such cascading effects, various studies suggested that peat OM decomposition will be enhanced by climate warming (Dorrepaal et al, 2009;Fenner and Freeman, 2011;Jassey et al, 2013). However, the studies were mainly conducted during the summer months, when environmental constraints, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these microhabitats are characterized by a different set of peat mosses and accompanying vascular plants (Saarnio et al, 1997;Rydin and Jeglum, 2006;Robroek et al, 2009) which ultimately control the quantity and quality of the organic matter available for microbial decomposition (Kettunen and Kaitala, 1996;Galand et al, 2003;Andersen et al, 2013;Jassey et al, 2013). In short, the composition of the methanogenic archaeal communities in peatlands shows a tight link with the microtopography in the peatland (Galand et al, 2003;Yavitt et al, 2011).…”
mentioning
confidence: 99%
“…increased variability in precipitation and increased temperature (IPCC, 2007), together with increasing N deposition loading (Phoenix et al, 2012) are believed to, directly or indirectly, affect the microtopography and the variables controlling the potential methane production. This may affect the methane emissions and the carbon allocation (Limpens et al, 2008;Luo and Weng, 2011;Jassey et al, 2013).…”
mentioning
confidence: 99%
“…Although this may be seen as a bias if the goal is to estimate proportions of individuals it may actually be an advantage for community ecology studies. Community ecology studies of testate amoebae are indeed increasingly based on biovolume-corrected community data obtained by direct microscopy (Jassey et al 2013).…”
Section: Discussionmentioning
confidence: 99%